THE TOBACCO INSTITUTE 940000 BUDGET (Tufts Archival Research Center, 2007)
Marginalia; Tobacco Institute (TI) budget for 1994, Federal/Issues Management Division. Includes issues of Media Relations, Excise Taxes, General Coalitions, and Advertising/Youth Programs. Edits indicate significant budget cuts.